The Interaction of Linguistic Worlds in Contemporary Russian Speech - Grigorian, Elena (Przegląd Wschodnioeuropejski, 2018)
The paper deals with alien linguistic elements in contemporary Russian speech on television. The analysis reveals the systematic character of their usage which serves particular pragmatic functions such as filling in lexical gaps, adding national color, etc. What presents the greatest interest are the cases showing that speakers are often aware of non-concurrence of lexical meanings (and conceptual systems) in different languages and even ascribe to the words from other languages new meanings and additional connotations they originally had not in the languages they come from (among the dominating ones are English, German, French and Italian, having the full scope of functions). Accordingly, today many native speakers of Russian (to different extent) live in several interacting linguistic worlds, using freely the resources of other languages, borrowing whatever they need for their mental model of the world.